Association study between microsatellite genotypes and layer performances in Rhode Island Red chicken* - DAS, ANANTA KUMAR; KUMAR, SANJEEV; RAHIM, ABDUL; KOKATE, LAXMIKANT SAMBHAJI (The Indian Journal of Animal Sciences, 2016)
This investigation aimed to study association between microsatellites and layer performances in Rhode Island Red selected line chicken. Genomic DNA samples isolated from the 12 randomly selected birds were investigated at 24 microsatellite loci. The microsatellite alleles were separated on 6% urea-PAGE and their molecular sizes were estimated. Locus specific alleles were identified according to their sizes, and their association with layer performance traits was assessed by least squares analysis of variance. Analysis revealed that age at sexual maturity of the birds had significant influence of 180bp/190bp and 184bp/196bp microsatellite genotypes in MCW0075 locus. Egg weight at 28th week of age was significantly associated with 210bp/244bp, 216bp/216bp, 216bp/238bp, 222bp/244bp genotypes in MCW0005; and 173bp/173bp, 175bp/175bp, 177bp/177bp in MCW0014. Egg production upto 40 weeks of age was also significantly associated with some genotypes in MCW0044 (133bp/151bp, 136bp/ 160bp), ADL0102 (136bp/166bp, 146bp/174bp, 166bp/166bp) and ADL0158 (178bp/214bp, 184bp/184bp, 184bp/ 214bp, 184bp/222bp). MCW0051 (90bp/118bp, 105bp/118bp, 118bp/118bp), MCW0014 (173bp/173bp, 175bp/ 175bp, 177bp/177bp) and ADL0176 (200bp/200bp, 200bp/236bp, 202bp/202bp) demonstrated significant influences on body weight at 40th week of age. Findings suggested faster genetic progress in RIR flocks by adapting microsatellite genotype based selection.